Ventricular tachycardia and acute myocardial infarction induced by coronary artery spasm in patient without coronary artery disease - Kartawan, Gabrielle Alexander; Kartawan, Tiffany Alexander (International Journal of Advances in Medicine, 2022)
Coronary artery spasm, marked by coronary vasoconstriction, is one of the etiologies of myocardial ischemia, often presenting as vasospastic angina. Vasospastic angina is diagnosed when angina which predominantly occurs at rest, is accompanied by ST-segment changes in ECG, or in the setting of borderline ECG changes, a positive provocation test through coronary angiography is required. Although coronary artery spasms could manifest in wide clinical settings, the occurrence of ventricular arrhythmias and acute myocardial infarction solely caused by spasms without evidence of prior coronary artery disease is rare. This case report is about a 46-year-old man who presented with ventricular tachycardia and acute myocardial infarction that later was found to be secondary to coronary vasospasm observed directly through coronary angiography. We aim to emphasize the importance of coronary artery spasms as the etiology of malignant ventricular arrhythmias and acute myocardial infarction manifestation. Optimization in treatment and prevention shall reduce future life-threatening complications of coronary artery spasms.